The Socio-Scientific Issues Approach as A Catalyst for Critical Thinking Skills in Elementary School - Nitte, Yulsy Marselina (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
This research aims to evaluate the effectiveness of the Socio-Scientific Issues (SSI) approach in improving students’ critical thinking skills within the context of 21st-century learning. The type of research employed in this study is quantitative research using a quasi-experimental approach with a non-equivalent control group design. The sample in this research consisted of 57 students. Data collection techniques included tests and observations. Data analysis involved normality testing, homogeneity testing, linearity testing, and hypothesis testing. The results of the normality test showed a significance value of 0.189 based on the Kolmogorov-Smirnov test. Since 0.189 > 0.05, it indicates that the data from both groups are normally distributed. The homogeneity test in the Test of Homogeneity of Variances table showed that both the experimental and control class data had a significance value of 0.567 > 0.05, indicating that the data are homogeneous. The linearity test results in the ANOVA table showed a significance value of 0.903 > 0.05, indicating that there is no deviation from a linear relationship between the independent and dependent variables. According the T-Test results, the significance value (sig. 2-tailed) was 0.000 < 0.05, which statistically indicates that the null hypothesis (H₀) is rejected. Therefore, it can be concluded that there is a significant effect of using the Socio-Scientific Issues (SSI) approach on improving students’ critical thinking skills. This means that a learning approach based on social issues examined through a scientific lens has proven to be effective in fostering the development of students’ critical thinking abilities.